2019
DOI: 10.1016/j.aim.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Measure complexity and Möbius disjointness

Abstract: In this paper, the notion of measure complexity is introduced for a topological dynamical system and it is shown that Sarnak's Möbius disjointness conjecture holds for any system for which every invariant Borel probability measure has sub-polynomial measure complexity.Moreover, it is proved that the following classes of topological dynamical systems (X, T ) meet this condition and hence satisfy Sarnak's conjecture: (1) Each invariant Borel probability measure of T has discrete spectrum.(2) T is a homotopically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 40 publications
1
100
0
Order By: Relevance
“…It is conjectured in [15] the converse of Proposition 4.5 is also true. If µ is ergodic, by [12, Corollary 39], we know that µ has discrete spectrum and if and only if µ is mean equicontinuous.…”
Section: 3mentioning
confidence: 87%
See 1 more Smart Citation
“…It is conjectured in [15] the converse of Proposition 4.5 is also true. If µ is ergodic, by [12, Corollary 39], we know that µ has discrete spectrum and if and only if µ is mean equicontinuous.…”
Section: 3mentioning
confidence: 87%
“…In [18] Katok introduced a notion using the modified notion of spanning sets with respect to an invariant measure µ and an error ε, which can be used to define the complexity function. In [2] Recently, in the investigation of the Sanark conjecture, Huang, Wang and Ye [15] introduced the measure complexity of an invariant measure µ similar to the one introduced by Katok [18], by using the mean metric instead of the Bowen metric (for discussion and results related to mean metric, see also [23,30]). They showed that if an invariant measure has discrete spectrum, then the measure complexity with respect to this invariant measure is bounded.…”
Section: Introductionmentioning
confidence: 99%
“…(X , T ) and showed that (X , T, µ) is µ-mean equicontinuous if and only if it has discrete spectrum, see also [20] for another proof. It should be noticed that recently the authors in [14,17] showed that for an invariant measure µ on a t.d.s. (X , T ), (X , T, µ) is µ-mean equicontinuous if and only if it has discrete spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In [3], Blanchard et al studied topological complexity via the complexity function of an open cover and showed that the complexity function is bounded for any open cover if and only if the system is equicontinuous. In [14,17], Huang et al studied topological and measure-theoretic complexity via a sequence of metrics induced by a metric and showed that an invariant measure µ on (X , T ) has bounded complexity with respect tod n if and only if (X , T ) is µ-mean equicontinuous if and only if it has discrete spectrum, whered n (x, y) = 1 n ∑ n−1 i=0 d (T i x, T i y). Ferenczi [5] studied measure-theoretic complexity of a m.p.s (X , B, µ, T ) using αnames of a partition and the Hamming distance.…”
Section: Introductionmentioning
confidence: 99%
“…for each ε ą 0 (here d n py, zq " 1 n ř n j"1 dpT j y, T j zq). The main result of the recent article [90] states the following:…”
Section: Sub-polynomial Complexitymentioning
confidence: 99%